Determination of predominant soluble salts in soils of the irrigation district Alto Chicamocha of Boyacá (2018)
In Boyacá, the Alto Chicamocha irrigation and drainage district (DRACH, by its initials in Spanish) is the department’s main agricultural production unit, covering an area of 8016.78 ha and due to the natural conditions and the management that has been given to the high basin of the Chicamocha River, salinization has been recognized as a limiting factor. Therefore, we sought to determine the predominant soluble salts in the soils that comprise the DRACH. Based on the chemical soil analysis information of 301 samples, obtained from studies conducted by GISSAT-UPTC and Corpoica, E.C, pH, anions and cations present in the soil were determined. For the spatial analysis of the variables studied, the ArcGis 10.3 software was used. Thirty-one water samples were collected in wells of thephreatimetric network to carry out the chemical characterization of the water. It was found that 48.01%of the soils of the district were non-saline, 22.93% slightly saline, 14.74% moderately saline and saline 14.33%. The main soluble salts in the soil were Na2SO4, Ca2SO4, NaCl2 and CaCl2, which are related to the lacustrine origin and the presence of thermal springs in the region. The areas with greater problem of salinization occur in the municipalities of Tibasosa, Patrocinio, Ucaca, Las Vueltas; in Santa Rosa de Viterbo in the village of Salitre; in Duitama in the villages Cebadero and Higueras with E.C. greater than 2 dS m-1.